Determinants of variations in breast milk protective factor concentrations of rural Gambian mothers. Issue 7 (July 1983) - Prentice, A; Prentice, A M; Cole, T J; Whitehead, R G
Abstract : The concentrations of 7 immunoproteins (IgA, IgG, IgM, the complement components C3 and C4, lactoferrin, and lysozyme) in the breast milk of 152 rural west African women were measured as part of a semilongitudinal study to assess their importance in infant health. Each mother maintained a characteristic level of production of immunoproteins relative to other mothers, and the concentration of each immunoprotein within each woman was correlated positively with the others. Parity was the major determinant of ranking and mothers of parity 1 and 2 produced the highest concentrations of immunoproteins. Except for lysozyme, infants' intake of these protective factors decreased in early lactation, but infants aged 1-2 years still received substantial amounts. The daily intakes by Gambian infants were similar to or higher than those of infants in Cambridge, United Kingdom. A marked seasonal increase in infant morbidity was not accompanied by an increase in the concentrations of protective factors in mothers' milk.